2019
DOI: 10.3201/eid2512.181225
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Bird-Virulent West Nile Virus Strain, Greece

Abstract: We report the full polyprotein genomic sequence of a West Nile virus strain isolated from Eurasian magpies dying with neurologic signs in Greece. Our findings demonstrate the local genetic evolution of the West Nile virus strain responsible for a human disease outbreak in the country that began in 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
1
12
1
Order By: Relevance
“…The two-year monitoring period of wild birds in Peloponnese Region demonstrated the inhabitation of resident, partial-migratory and migratory species in different ecological niches. During field work, massive deaths or presence of birds displaying neurological signs, especially of magpies, were not described in contrast to the previously reported findings from the Regional Unit of Argolida in 2017 [33].…”
Section: Discussioncontrasting
confidence: 83%
“…The two-year monitoring period of wild birds in Peloponnese Region demonstrated the inhabitation of resident, partial-migratory and migratory species in different ecological niches. During field work, massive deaths or presence of birds displaying neurological signs, especially of magpies, were not described in contrast to the previously reported findings from the Regional Unit of Argolida in 2017 [33].…”
Section: Discussioncontrasting
confidence: 83%
“…In comparison free-ranging goshawks (Accipiter gentilis) infected with lineage 2 WNV predominantly had CNS lesions and abundant WNV antigen detection in foci associated with lesions, in addition to severe myocarditis and lesions in the liver, spleen, and kidney [40]. Additionally, free-living magpies infected with WNV L2 showed severe CNS signs while, in contrast, experimentally infected red-legged partridges, our study species, had only non-specific signs and macroscopic lesions similar as those observed in WNV L1-infected birds, although in both studies no histopathologic descriptions were included [12,41]. This suggests, on the one hand, that bird-virulent WNV L2 strains may be more neurovirulent while, on the other hand, as reported by other authors [18], WNV pathogenesis may be highly dependent on both the infecting strain and the avian host species.…”
Section: Discussionmentioning
confidence: 62%
“…In the Mediterranean basin, WNV activity is continuously increasing, and has been associated with several outbreaks affecting mainly humans and horses [4,5]. In this area, avian mortality due to WNV lineage 1 (L1) has been sporadic, while lineage 2 (L2) WNV has been responsible for significant outbreaks in central Europe and in magpies in Italy and Greece [6][7][8][9][10][11][12][13]. Nevertheless, under laboratory conditions in experimental infections, at least some Mediterranean L1 WNV strains have proven to be pathogenic for European wild bird species [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The magpie, one of the most abundant corvids in Europe [ 18 ], has recently been shown to be highly susceptible to WNV infection and a possible source for virus transmission [ 19 ], and the mortality of magpies due to lineage 2 WNV has been reported in Greece [ 20 ]. However, there are scarce data on the susceptibility of magpies to USUV infection.…”
Section: Introductionmentioning
confidence: 99%